2018
DOI: 10.1186/s13049-018-0486-1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma facilities in Denmark - a nationwide cross-sectional benchmark study of facilities and trauma care organisation

Abstract: BackgroundTrauma is a leading cause of death among adults aged < 44 years, and optimal care is a challenge. Evidence supports the centralization of trauma facilities and the use multidisciplinary trauma teams. Because knowledge is sparse on the existing distribution of trauma facilities and the organisation of trauma care in Denmark, the aim of this study was to identify all Danish facilities that care for traumatized patients and to investigate the diversity in organization of trauma management.MethodsWe cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Yet all cardiac arrest cases, regardless of the cause, are treated according to the European Resuscitation Council guidelines [ 12 ]. A TCA will result in the activation of a trauma team within one of the four Level 1 trauma centres as defined by the Danish Health Authorities [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Yet all cardiac arrest cases, regardless of the cause, are treated according to the European Resuscitation Council guidelines [ 12 ]. A TCA will result in the activation of a trauma team within one of the four Level 1 trauma centres as defined by the Danish Health Authorities [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of national HEMS in 2014 and centralization may have enlarged the catchment area. In 2018, Weile et al found heterogenous composition of the trauma team and TTA criteria at trauma facilities in Denmark (33) and some major trauma patients are still treated at acute-care hospitals in Central Denmark Region. A national benchmark study including the entire Danish trauma patient population is warranted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Furthermore, previous studies have been designed for specific evaluations such as the heart or the lungs [5,[12][13][14][15][16][17][18]. These patients only represent a small sample of the patients seen in the ED [19][20][21].…”
Section: Introductionmentioning
confidence: 99%